Analisis Pengaruh Preferensi Konsumen Terhadap Minat Beli Produk Minuman Kopi di Pit Stop Kopi Kawasan Industri Gresik (KIG) - Sella Kumala Sari; Rahmad Jumadi; Raden Achmad Djazuli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of consumer preferences on interest in purchasing coffee beverage products at Pit Stop Kopi KIG. Consumer preferences studied include price, menu variations, location and product attributes. This research uses quantitative methods using multiple linear regression analysis. Data was obtained from 120 respondents who were Pit Stop Coffee consumers. The research results show that simultaneously, consumer preferences consisting of price, menu variations, location and product attributes have a significant effect on interest in buying coffee drinks. Partially, menu variations and product attributes have a significant effect on purchase intention, while price and location do not have a significant effect. The conclusion of this research is that Pit Stop Kopi needs to increase menu variations and maintain and improve product attributes to attract consumer buying interest. Future research can explore other factors that influence consumer purchasing interest and expand the scope of the sample to obtain more comprehensive results.